Rational design of coumarin derivatives as antituberculosis agents - Mali, Hemlata M.; Sabale, Sandip S.; Degani, Mariam S.; Borkute, Rachana; Choudhari, Amit S.; Sarkar, Dhiman; Krishna, Vagolu Siva; Sriram, Dharmarajan (Future Medicinal Chemistry, 2018)
A series of coumarin derivatives was designed as potential antituberculosis agents. Results: The compounds were screened against active and dormant Mycobacterium tuberculosis (Mtb). Compounds 3k and 3n were found to have the most promising activity against replicating MtbH37Rv exhibiting minimum inhibitory concentration of 4.63 and 9.75 mu M respectively. The compounds were also effective against dormant MtbH37Rv exhibiting more potency than the standard drugs, isoniazid and rifampicin. The compounds were found to be non-cytotoxic against human cell lines. Conclusion: This study provides promising antituberculosis agents that are effective against replicating as well as dormant Mtb and can thus act as potential leads for further development.

Synthesis and biological evaluation of some new tricyclic pyrrolo[3,2-e]tetrazolo[1,5-c]pyrimidine derivatives as potential antitubercular agents - Patil, Yogesh; Shingare, Ramesh; Choudhari, Amit; Borkute, Rachana; Sarkar, Dhiman; Madje, Balaji R. (Archiv Der Pharmazie, 2018)
A series of new tricyclic pyrrolo[3,2-e]tetrazolo[1,5-c]pyrimidines 8a-l were synthesized and characterized by IR, NMR (H-1 and C-13), and mass spectral analysis. The newly synthesized compounds 8a-l were inspected for their in vitro antitubercular activity against Mycobacterium tuberculosis (MTB) H37Ra using an established XTT reduction menadione assay (XRMA). The title compounds exhibited minimum inhibitory concentrations (MIC90) ranging from 0.09 to >30g/mL. Five compounds (8c, 8i-l) were further confirmed for their dose-dependent effect against MTB. These compounds were evaluated in the THP-1 infection model, where 8i (MIC90=0.35g/mL), 8j (MIC90=1.17g/mL), 8k (MIC90=2.38g/mL), and 8l (MIC90=1.17g/mL) demonstrated significant antitubercular activity. All the ex vivo active compounds showed insignificant cytotoxicity against the human cancer cell lines, HeLa, MCF-7, and THP-1. Inactivity of all these compounds against Gram positive and Gram negative bacteria indicates their specificity. Molecular docking studies in the active site of the sterol 14alpha-demethylase (CYP51) enzyme revealed a similar binding mode to the native ligand in the crystal structure, thereby helping to understand the ligand-protein interactions and to establish a structural basis for inhibition of MTB. The results suggest novel pharmacophores as selective and specific inhibitors against MTB that can be explored further to synthesize lead compounds against tuberculosis. In summary, the results clearly indicate the identification of some novel, selective, and specific inhibitors against MTB that can be explored further for potential antitubercular drugs.
Keywords: 2-e]tetrazolo[1; 5-c]pyrimidine; Antituberculosis; Cytotoxicity; Molecular docking; tricyclic pyrrolo[3